Blueprint : Lovetics Enterprise “Tropicae Miracle” / Akmal Hakim Adanan ... [et al.] - Adanan, Akmal Hakim; Ahmad Zafwan, Nurul Anis Khairunnisa; Hamdan, Nur Syuhada; Mohamed Shafie, Nur Aida Husna; Zulkofli, Nurul Syazana (2019)
It is known that the daily concerns for the fish keeper or fish lovers are that their fish might die due to the health problem or anything related that can cause their fish to die. Therefore, we believe that the benefits of Terminalia Catappa must be already known among fish keeper. T enninalia Catappa is known as natural sources that can help fish from getting sick since it acts as a bacteria killer and treats wounds. Besides, it also can lower pH value, create a cozy and comfortable atmosphere for the fish, help to encourage the growth of beautiful tails, removes damaged fins, tails and skin. However, from our observation and research on our previous case study, the main problem that every fish keepers must deal with the existing Catappa's product is they need to pick up the leftover substances from teabag. Other problems are the existing product such as black water is quite expensive and the aquarium tank becomes darker when excessive use of black water. There are people that might think that their aquarium tank looks dirty. The last problem that we found out, if Catappa leaves were used in an aquarium tank, they will need to pick up the leaves back to change into other new leaves. Thus, this study was conducted to help the fish keepers, especially for those people, involve in aquatic business and people that have fish as their pets to overcome their problems.